2011
DOI: 10.1159/000327765
|View full text |Cite
|
Sign up to set email alerts
|

Electric-Acoustic Stimulation of the Auditory System: A Review of the First Decade

Abstract: Electric-acoustic stimulation (EAS) was developed for individuals with a profound hearing loss in the high frequencies and a substantial residual low-frequency hearing (LFH). For this group of candidates, conventional hearing aids often neither provided sufficient amplification nor were they considered suitable for cochlear implantation due to the possible destruction of residual hearing capabilities. With EAS, combining electric stimulation with an ipsilateral acoustic stimulation, preservation of residual LF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
90
1
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(99 citation statements)
references
References 341 publications
1
90
1
6
Order By: Relevance
“…The continuing success of cochlear implants (CIs) in recent years (Patrick et al, 2006;Hochmair et al, 2006) and the consequent expansion of the range of indications for recipients of such devices (Laszig et al, 2004;Lenarz et al, 2009;Arndt et al, 2011;von Ilberg et al, 2011) call for improved audiometric measuring techniques in order to ensure adequate quality of understanding speech when using the CIs. CI recipients need life-long support to maintain their CI system postimplant.…”
mentioning
confidence: 99%
“…The continuing success of cochlear implants (CIs) in recent years (Patrick et al, 2006;Hochmair et al, 2006) and the consequent expansion of the range of indications for recipients of such devices (Laszig et al, 2004;Lenarz et al, 2009;Arndt et al, 2011;von Ilberg et al, 2011) call for improved audiometric measuring techniques in order to ensure adequate quality of understanding speech when using the CIs. CI recipients need life-long support to maintain their CI system postimplant.…”
mentioning
confidence: 99%
“…A inserção do conjunto na rampa timpânica deve causar o menor dano possível às estruturas internas da cóclea para não prejudicar a audição residual do paciente (Carlson et al, 2012;Ilberg et al, 2011). No caso de ossificação da cóclea, fica dificultada a inserção dos eletrodos até a profundidade necessária para estimular regiões relativas a sons de baixa frequência.…”
Section: Estimulaçãounclassified
“…Neste caso, o processador de áudio deve desempenhar tanto as funções de geração de código de pulsos quanto as etapas presentes em próteses auditivas convencionais, como síntese de áudio e cancelamento de realimentação, além dos blocos de redução de ruído, presentes em todos os tipos de próteses auditivas. A estimulação eletroacústica possibilita que pacientes sejam beneficiados tanto pela audição via estimulação elétrica quanto pela audição natural remanescente, que lhe garante melhor qualidade (Ilberg et al, 2011). Percepção musical (Kong et al, 2005) e reconhecimento de fala na presença de ruído (Kiefer et al, 2005) são relatados como melhores em pacientes com estimulação eletroacústica do que com apenas elétrica.…”
Section: Estimulação Eletroacústicaunclassified
See 1 more Smart Citation
“…As selection criteria for CI recipients have eased, more patients with preserved low frequency hearing have received CIs (for review see Turner et al, 2008). Several clinical studies report improvement of overall hearing performance of subjects with residual hearing in one ear (possibly with a hearing aid) in addition to ICES in the other, sometimes referred to as bimodal hearing (Von Ilberg et al, 2011, Mok et al, 2006, Firszt et al, 2008, Ching et al, 2006). For example, Dorman et al (2007) showed an increase of 20% in performance of patients with CI in one ear and a hearing aid in another on word and sentence recognition tasks when electric stimulation was added (EAS).…”
Section: Introductionmentioning
confidence: 99%